Prevalence of anemia and its relationship with mother’s age and gestational age in pregnant women visiting Yahyanejad hospital of Babol in 2000 - N Asnafi; S Sina; SM Miri (JRI, 2003)
According to World Health Organization (WHO) report, anemia is the most common disease related to nutritional defects, which affects about 2 Billion people in the world, and among this huge population, children and pregnant women are the two major high risk groups. The purpose of the present study was to determine the prevalence of anemia in pregnant women and it’s relationship to mother’s age and gestational age. This study was done on 214 pregnant women visiting Yahyanejad Gyn & Obs clinic, during the period of March - Aug 2000. Complete Blood Count (CBC) was done at the first visit and if Hemoglobin (Hb) was less than 11mg/dl in first & third trimester or less than 10.5 in the 2nd trimester, they were considered to have the anemia of pregnancy. For diagnosis the type of anemia, the other lab tests were done. Frequency of anemia in different age groups and mean pregnancy trimester were studied. Mean age of cases was 24.6 ± 5 years old and hemoglobin was 12.6 ± 1.6. mg/dl overall, 20 (9.4%) pregnant women had anemia, the highest frequency of anemia (12.78%) was seen in women at 21-30 year old group. Frequency of anemia in high risk pregnancies (mother’s age of less than 18 & more than 35 years old ) was less than normal age group (19-34 years old ) (P< 0.05).Anemia was more common in third trimester than first & second trimesters.(P<0.05).Iron dificiency anemia was the most common anemia in pregnant women. Due to higher frequency of anemia in third trimester, it is highly advisable to start iron replacement therapy from second trimester and the mather’s Hematocrit level be checked at early third trimester.
Keywords: Anemia, Pregnancy, Gestational age, Age, Hemoglobin, Prevalence